2017
DOI: 10.1038/s41598-017-06008-2
|View full text |Cite
|
Sign up to set email alerts
|

Sca-1 identifies a trophoblast population with multipotent potential in the mid-gestation mouse placenta

Abstract: Trophoblast stem (TS) cells in the mouse derive from the polar trophectoderm of the blastocyst and persist through early gestation (to E8.5) to support placental development. Further development and growth is proposed to rely on layer-restricted progenitor cells. Stem cell antigen (Sca) -1 is a member of the Ly6 gene family and a known marker of stem cells in both hematopoietic and non-hematopoietic mouse tissues. Having identified that Sca-1 mRNA was highly expressed in mouse TS cells in culture, we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…However, the exact anatomical location of hTSCs in vivo in both the early placenta and the TE is still unclear. Likewise, while mouse TSCs can be derived from both the TE and the chorion prior to E11.5, and can be differentiated to all trophoblast populations, further investigation is needed to understand which murine trophoblast population they resemble in vivo and how they relate to human TSCs (Natale et al, 2017;Tanaka et al, 1998). Single cell RNA-sequencing has now been performed on the mouse mid-gestation placenta and on human term placenta, as well as on these placentas early in their development (Liu et al, 2018;Nelson et al, 2016;Pavlicěv et al, 2017;Suryawanshi et al, 2018;Vento-Tormo et al, 2018).…”
Section: Trophoblast Stem Cells and Organoidsmentioning
confidence: 99%
“…However, the exact anatomical location of hTSCs in vivo in both the early placenta and the TE is still unclear. Likewise, while mouse TSCs can be derived from both the TE and the chorion prior to E11.5, and can be differentiated to all trophoblast populations, further investigation is needed to understand which murine trophoblast population they resemble in vivo and how they relate to human TSCs (Natale et al, 2017;Tanaka et al, 1998). Single cell RNA-sequencing has now been performed on the mouse mid-gestation placenta and on human term placenta, as well as on these placentas early in their development (Liu et al, 2018;Nelson et al, 2016;Pavlicěv et al, 2017;Suryawanshi et al, 2018;Vento-Tormo et al, 2018).…”
Section: Trophoblast Stem Cells and Organoidsmentioning
confidence: 99%
“…It has been shown in the rat placenta that proliferation is highest in the labyrinth at E10-11 and has dropped to a basal level by E16 60 . At E19.5, proliferating cells are much less likely to be observed; however, as proliferation can be altered in response to placenta stress 61 , it was evaluated to see whether, the rate of proliferation, albeit low, was changed. The increased size was neither attributed to an increase in proliferation, as the number of Ki67 + nuclei was not altered (Fig.…”
Section: Fetal/placental Outcomementioning
confidence: 99%
“…The TSCs continue to proliferate and differentiate during the growth and development of the placenta to form other types of TCs, suggesting that TSCs have the property of stem cells [49][50][51][52][53][54]. TSCs are a heterogeneous population of cells with both differentiated and undifferentiated phenotypes [55]. Natale et al found that undifferentiated trophoblasts, from mid-gestation mouse placentas, expressed the murine cell surface protein Sca1.…”
Section: Discussionmentioning
confidence: 99%
“…Natale et al found that undifferentiated trophoblasts, from mid-gestation mouse placentas, expressed the murine cell surface protein Sca1. The Sca1 + subpopulation of TCs demonstrated proliferation and multipotency with differentiation into TC types of both the junctional zone and the labyrinth layer [55]. In an attempt to identify a homogeneous subpopulation of undifferentiated TSCs in the near-term placenta with the potential application for isolation of these cells from mouse, and human placentas in the future, we assessed TSCs for the expression of CD117, a cell surface marker of stem/progenitor cells [30,31].…”
Section: Discussionmentioning
confidence: 99%